The Creation in Building Good News for The Society in Medan, Indonesia - Ahmad Qorib; M. Yoserizal Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The news has three news coverage techniques, namely reportage, interviews, library research (literature studies). Some news writing techniques that can be a basic guide for journalists are:The title of the news is as concise as possible with short and clear sentences, but can still describe the core of the story as a whole.There are 5W + 1H elements.Arrange news so that it can be presented with accurate, clear and interesting information. Use language that is easily understood by readers from a variety of circles.Not "patronizing" but "showing / presenting".